1998
DOI: 10.1182/blood.v91.8.2991.2991_2991_2997
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Malignancies Demonstrate Loss-of-Function Mutations ofBAX

Abstract: The BCL-2 gene family regulates the susceptibility to apoptotic cell death in many cell types during embryonic development and normal tissue homeostasis. Deregulated expression of anti-apoptotic BCL-2 can be a primary aberration that promotes malignancy and also confers resistance to chemotherapeutic agents. Recently, studies ofBax-deficient mice have indicated that the pro-apoptotic BAX molecule can function as a tumor suppressor. Consequently, we examined human hematopoietic malignancies and found that appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0
8

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(93 citation statements)
references
References 32 publications
1
84
0
8
Order By: Relevance
“…Although Gutierrez et al (1999) suggested that defects in Bax might contribute to FAS resistance in BL, and we and others have identified Bax mutations in BL cell lines (Brimmell et al, 1998;Meijerink et al, 1998;Gutierrez et al, 1999), the expression of Bax and other Bcl-2 family proteins did not correlate with TRAIL sensitivity (Spender et al, 1999). Other potential mechanisms of resistance that might account for TRAIL resistance include altered expression of other regulatory molecules, such as death-associated protein 3 (DAP3) (Miyazaki & Reed, 2001).…”
Section: Discussionmentioning
confidence: 67%
“…Although Gutierrez et al (1999) suggested that defects in Bax might contribute to FAS resistance in BL, and we and others have identified Bax mutations in BL cell lines (Brimmell et al, 1998;Meijerink et al, 1998;Gutierrez et al, 1999), the expression of Bax and other Bcl-2 family proteins did not correlate with TRAIL sensitivity (Spender et al, 1999). Other potential mechanisms of resistance that might account for TRAIL resistance include altered expression of other regulatory molecules, such as death-associated protein 3 (DAP3) (Miyazaki & Reed, 2001).…”
Section: Discussionmentioning
confidence: 67%
“…It has been reported that Bax induction alone induces apoptosis in Jurkat cells, 5) but Jurkat cells have a Bax gene mutation and do not express Bax protein. 6) Cancer cells express different levels of proapoptotic Bax protein. 6) The present study demonstrated that Bax induction alone initiated cytochrome c release from mitochondria, activation of caspase 3 and apoptosis to some extent in DLD-1 cells, which originally express a high level of proapoptotic Bax protein.…”
Section: Discussionmentioning
confidence: 99%
“…6) Cancer cells express different levels of proapoptotic Bax protein. 6) The present study demonstrated that Bax induction alone initiated cytochrome c release from mitochondria, activation of caspase 3 and apoptosis to some extent in DLD-1 cells, which originally express a high level of proapoptotic Bax protein. Recently, a pathway between Bax induction and caspase-3 activation has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bax is often mutated in human colorectal and hematopoietic malignancies. 41,42 In mice, loss of Bax promotes tumor formation. 43 Bax has also been shown to have a role in DNA damage-induced PCD.…”
Section: Baxmentioning
confidence: 99%